OPTIMIZING FORMULATION OF MINI TABLETS FLOATING RANITIDINE HCL USING FULLY PREGELATINIZED STARCH (MANIHOT ESCULENTA CRANTZ) WITH SIMPLEX LATTICE DESIGN - Dewantara Putra, I. Gusti Ngurah Agung; MURWANTI, RETNO; ROHMAN, ABDUL; SULAIMAN, T. N. SAIFULLAH (International Journal of Applied Pharmaceutics, 2019)
Objective: The main objective of this study was to optimize the noneffervescent floating mini tablets (NEFT) formula of ranitidine hydrochloride (ranitidine HCl) using the simplex lattice design (SLD) with parameters, granule flow rate, hardness, friability, floating lag time and ranitidine HCl dissolution test (%). Methods: The material was prepared using the SLD model was cassava starch fully pregelatinized (CSFP), hydroxypropyl methylcellulose K4M (HPMC K4M), and magnesium stearate. The formula obtained was tested for critical parameters, namely flow rate, hardness, friability, floating lag time and ranitidine HCl dissolution test (%). The dissolution test was carried out by using the USP type II method (paddle method). The beaker is immersed in the water bath of temperature 37 °C. It is filled with 900 ml of 0.1 N HCl, and the apparatus was set at 75 rpm. The samples were taken in the interval of 10 min and estimated content by a spectrophotometer at 312 nm. Results: The optimum formula based on superimposed graphs of various contour plots with SLD. From the experimental data for all test parameters, the experimental results are approaching with the results of the prediction. The condition for optimum functional components in NEFT was 80 mg for CSFP, HPMC K4M 30 mg, and 10 mg magnesium stearate to obtain a yield of 7.85 kg hardness, 0.34 % friability, 15.27 floating lag time and 91.31 % ranitidine HCl dissolved. Conclusion: It can be concluded that the optimum formula using the Design-Expert® program the SLD concept is obtained in the range of 70-80 mg CSFP, 30-40 mg HPMC K4M, 0-10 mg magnesium stearate.